The Dual PI3K/mTOR Pathway Inhibitor GDC-0084 achieves antitumor activity in PIK3CA-Mutant breast cancer brain metastases - Ippen, Franziska M. (Clinical cancer research, 2019)
Purpose: Previous studies have shown that the PI3K/Akt/mTOR pathway is activated in up to 70% of breast cancer brain metastases, but there are no approved agents for affected patients. GDC-0084 is a brain penetrant, dual PI3K/mTOR inhibitor that has shown promising activity in a preclinical model of glioblastoma. The aim of this study was to analyze the efficacy of PI3K/mTOR blockade in breast cancer brain metastases models. Experimental Design: The efficacy of GDC-0084 was evaluated in PIK3CA-mutant and PIK3CA wild-type breast cancer cell lines and the isogenic pairs of PIK3CA wild-type and mutant (H1047R/+) MCF10A cells in vitro. In vitro studies included cell viability and apoptosis assays, cell-cycle analysis, and Western blots. In vivo, the effect of GDC-0084 was investigated in breast cancer brain metastasis xenograft mouse models and assessed by bioluminescent imaging and IHC. Results: In vitro, GDC-0084 considerably decreased cell viability, induced apoptosis, and inhibited phosphorylation of Akt and p70 S6 kinase in a dose-dependent manner in PIK3CA-mutant breast cancer brain metastatic cell lines. In contrast, GDC-0084 led only to growth inhibition in PIK3CA wild-type cell lines in vitro. In vivo, treatment with GDC-0084 markedly inhibited the growth of PIK3CA-mutant, with accompanying signaling changes, and not PIK3CA wild-type brain tumors. Conclusions: The results of this study suggest that the brain-penetrant PI3K/mTOR targeting GDC-0084 is a promising treatment option for breast cancer brain metastases with dysregulated PI3K/mTOR signaling pathway conferred by activating PIK3CA mutations. A national clinical trial is planned to further investigate the role of this compound in patients with brain metastases.
Gesehen am 17.09.2019